Popular Education and Critical Pedagogy: Freire’s pedagogical principles in the training of Popular Health Educators (Práxis Educativa, 2021)
This article, derived from a qualitative research, presents the pedagogical organization of a Training and Improvement Course for Popular Health Educators in the Unified Health System (Sistema Único de Saúde - SUS), in order to verify, in this planning, the presence of the principles of the National Policy on Popular Education in Health (Política Nacional de Educação Popular em Saúde - PNEP-SUS). The PNEP-SUS is based on the theoretical and methodological conceptions of Popular Education inspired by the Critical Pedagogy and Paulo Freire’s work. The analysis carried out identified the following principles: Dialogue; Shared construction of knowledge; Lovingness; Problematization; Construction of the democratic and popular design; Non-hierarchical coexistence; and emancipation, which guided the planning of the didactic activities of the course. The study showed that the strategies of the Popular Education in Health, based on Freire’s work, can promote popular participation, participatory management, the exercise of social control and health care.Keywords: Popular Education in Health. Paulo Freire. Critical Pedagogy.